Strengthening MSMEs: Evaluating the Impact of Sharia Rural Banks on Welfare in Accordance with Maqashid Sharia - Suryaman, Inge Salsabila; Mariyanti, Tatik; Anugrah, Insan Praditya (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2024)
This study aims to evaluate the support provided for MSME development by PT. BPRS Hijra Alami and the application of maqashid sharia principles in its management. The research employs a qualitative method, using data collection techniques such as observation, interviews, and financial report analysis. The main findings reveal significant limitations in the support for training programs and business network access for MSMEs. Although BPRS provides financing, additional support such as skills training and network access remains inadequate, affecting the ability of MSMEs to utilize funds and expand their business networks optimally. The study also uncovers that, despite the application of maqashid sharia principles in BPRS's management, their implementation has not been fully effective in managing the risks and social impacts of the provided financing. The primary contribution of this research is the emphasis on the need for a more comprehensive integration of maqashid sharia principles throughout all operational aspects of BPRS, as well as offering recommendations for policies supporting MSME training and network access. This study provides new insights into Islamic banking practices and MSME development and suggests directions for future research to examine the effectiveness and social impact of the implemented strategies